2017
DOI: 10.21106/ijtmrph.48
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Preconception Care Seeking Practices among Reproductive-age Diabetic Women in Zambia

Abstract: Background and Objectives: Pre-existing diabetes is associated with poor pregnancy outcomes, yet much is unknown about knowledge of preconception care among diabetic women. The objective of this study was to examine the knowledge and preconception care seeking practices of diabetic women in the reproductive age. Methods: A cross- sectional hospital based study of 114 diabetic women between 15-45 years old was conducted between March and May 2017. Data was collected using structured questionnaires in face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 0 publications
1
22
2
Order By: Relevance
“…However, this study was lower than the study conducted in Zambia (47.4%). 30 This might be due to the difference in the study population. The study from Zambia was conducted on patients with diabetes on follow-up and frequent contact with healthcare providers increases the chance of obtaining information.…”
Section: Open Accessmentioning
confidence: 98%
“…However, this study was lower than the study conducted in Zambia (47.4%). 30 This might be due to the difference in the study population. The study from Zambia was conducted on patients with diabetes on follow-up and frequent contact with healthcare providers increases the chance of obtaining information.…”
Section: Open Accessmentioning
confidence: 98%
“…Results from this study showed fair knowledge though with poor practice of seeking preconception care. Contrary to a poor knowledge level as well as poor practice of seeking preconception care reported in a study conducted in Zambia [17]. Another study in Ethiopia also found that level of women's knowledge of preconception care is relatively low [14].…”
Section: Discussionmentioning
confidence: 80%
“…Health promotion, self-care may be necessary for promoting PCC (9). Many studies on PCC conducted among women visiting hospitals also reported similarly low levels of knowledge (10)(11)(12)(13)(14)(15)(16). In a study in the United States of America (USA), lack of knowledge was identified as the most crucial barrier to the practice of preconception behavior, the second most crucial barrier was the cost (17).…”
Section: Discussionmentioning
confidence: 99%
“…Women in the USA have low to moderate knowledge of issues related to preconception health (24). The proportion of women knowing PCC varied from 7 to 85% in different countries (11,12,14,15,(25)(26)(27). Usually, most of the women have a positive attitude toward seeking PCC (14,16,22,26).…”
Section: Preconception Services: Knowledge and Utilizationmentioning
confidence: 99%
See 1 more Smart Citation